ZF21 is a new regulator of focal adhesion disassembly and a potential member of the spreading initiation center - Nagano, Makoto (Landes Bioscience, 2011)
Adherent cells migrate on extracellular -matrices (ECM) by repeated spreading and contraction of the cell body. Focal adhesions (FAs) play a major role in the adherence of cells to the ECM and in the generation of the cellular forces that maintain morphology and allow cells to move. FAs also mediate bidirectional transmembrane signals in conjunction with growth factor receptors and signaling molecules. Although the mechanisms that regulate cell migration are not yet fully understood, the regulation of the formation and turnover of FAs is a key factor determining the rate and direction of cell migration. We recently identified a component of FAs termed ZF21, which is a member of a family of proteins characterized by the presence of a conserved phosphoinositide-binding motif. ZF21 promotes dephosphorylation of FAK at Tyr(397) upon microtubule extension to FAs and thereby regulates the disassembly of FAs in a microtubules-dependent manner. To obtain further insight into the regulation of cell adhesion by ZF21, we analyzed proteins associated with ZF21 by proteomic analysis. We identified 45 proteins including FA-related proteins and multiple RNA binding proteins that have been shown recently to be components of the spreading initiation center (SIC). SICs are cell adherent structures that can be observed only in the early stages of cell spreading and have been implicated in regulating the rate of cell spreading. In this article, we report new ZF21-binding proteins identified by proteomic analysis and discuss the potential functions of ZF21 in regulating disassembly of FAs.